2021
DOI: 10.3390/pr10010053
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Description of Jet and Duct Ventilation in Underground Garage after LPG Dispersion

Abstract: Contamination of toxic and odorous gases emitted from stacks in buildings located in an urban environment are potential health hazards to citizens. A simulation using the computational fluid dynamic technique may provide detailed data on the flammable region and spatial dispersion of released gases. Concentrations or emissions associated with garage sources and garage-to-house migration rates are needed to estimate potential exposures and risk levels. Therefore, the aim of the study was to use an original math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Once the LPG tank trailer fails in the expressway, the LPG will undergo a rapid depressurization process. It is noticed that the leaked LPG will gather in the depressions of the ground, which becomes a highly risky zone for the safety of the road transport [4]. In the LPG dispersion process, it is found that the ventilation factor is the key to reducing fire or explosion risk in buildings [5].…”
Section: Introductionmentioning
confidence: 99%
“…Once the LPG tank trailer fails in the expressway, the LPG will undergo a rapid depressurization process. It is noticed that the leaked LPG will gather in the depressions of the ground, which becomes a highly risky zone for the safety of the road transport [4]. In the LPG dispersion process, it is found that the ventilation factor is the key to reducing fire or explosion risk in buildings [5].…”
Section: Introductionmentioning
confidence: 99%